Penggunaan Media Nitasapura untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas II SD Negeri 6 Dauhwaru - Ni Luh Putu Yus Ani (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
This study is a classroom action research aims to increase the activity and learning achievemen making use of Nitasapura. Subject of the study is the 34 first semester students of the second graders SD Negeri 6 Dauhwaru academic year 2018/2019. Technique of collecting data applied in this study is observation and test to obtain the data on students’ learning activities and learning achievement. The collected data were presented qualitatively applying a comparative descriptive technique. The use of Nitasapura in mathematics teaching and learning may increase students’ activities in learning mathematics; before the treatment it is at the category of less active learning, and it becomes an active category at the end of the treatment. The use of Nitasapura improves the students learning achievement of the second graders at SD Negeri 6 Dauhwaru for the topic of number. This fact can be observed from result of the first cycle average test score which is 66.6, it is in everage category with 73.53% learning achievement. Meanwhile, the average test score of the second cycle is 82.4, at good category with 100% learning achievement. Based on these facts, it is to say that the use of Nitasapura in mathematics teaching and learning increases the activities and learning achievement of the second graders at SD Negeri Dauhwaru 6.